Effects of rearing systems on the eggshell quality, bone parameters and expression of genes related to bone remodeling in aged laying hens - Fu, Yu; Wang, Jing; Schroyen, Martine; Chen, Gang; Zhang, Hai-jun; Wu, Shu-geng; Li, Bao-ming; Qi, Guang-hai (Frontiers in Physiology, 2022)
Public concerns regarding animal welfare are changing the selection of rearing systems in laying hens. This study investigated the effects of rearing systems on eggshell quality, bone parameters and relative expression levels of genes related to bone remodeling in aged laying hens. A total of 2,952 55-day-old Jing Tint Six pullets were randomly assigned to place in the conventional caging system (CCS) or aviary system (AVS) and kept until 95 weeks of age. The AVS group delayed the decrease of eggshell quality and alleviated the symptoms of osteoporosis in the humerus rather than in the femur. Eggshell breaking strength, thickness, weight, weight ratio, stiffness and fracture toughness were decreased linearly with age (from 55 to 95 weeks of age, p < 0.05). The AVS group had higher eggshell breaking strength, stiffness and fracture toughness than the CCS group (p < 0.05). Higher total calcium and phosphorus per egg were presented in the AVS group at 95 weeks of age (p < 0.05). At 95 weeks of age, the AVS group had a humerus with higher weight, volume, length, midpoint perimeter, cortical index, fat-free dry weight, ash content, total calcium per bone, total phosphorus per bone, average bone mineral density, strength, stiffness and work to fracture compared to the CCS group (p < 0.05). Such differences did not appear in the femur. The relative expression levels of alkaline phosphatase (ALP) and osteocalcin (OCN) genes in the femur and hormone receptors (vitamin D receptor (VDR), estrogen receptor alpha (ERα) and fibroblast growth factor 23 (FGF23)) genes in the humerus were significantly upregulated (p < 0.05) in the AVS group. The level of tartrate-resistant acid phosphatase (TRAP) transcripts was also increased (p < 0.05) in the femur of the AVS group. Overall, compared with the CCS, the AVS alleviated the deterioration of eggshell and bone qualities of aged laying hens, which may be related to the changes in the expression of genes associated with bone remodeling.